Tropical Indo‐Pacific Compounding Thermal Conditions Drive the 2019 Australian Extreme Drought - Wenjun Zhang; Wei Mao; Feng Jiang; Malte F. Stuecker; Fei‐Fei Jin; Li Qi (Geophysical Research Letters)
Abstract Australia suffered a long‐lasting extensive drought in 2019 with catastrophic wildfires creating about $4.4 billion damages, the worst record in the recent four decades. Concurrent with this extreme drought, the tropical Indo‐Pacific oceans exhibited an extraordinary combination of sea surface temperature (SST) anomalies, characterized by a Central‐Pacific (CP) El Niño event with westernmost location and the third strongest positive Indian Ocean Dipole (IOD) event. We here show evidence that this unique combination was responsible for the pan‐Australian drought as a westward located CP El Niño event and a strong positive IOD event can exacerbate precipitation reduction in northeastern and southern Australia, respectively. These continent‐wide extreme droughts could become more frequent over Australia in a warming world, considering projected increases in both CP El Niño and extreme positive IOD events superimposed on secular warming and drying trends.